PENGALAMAN SISWA DALAM MENGIKUTI PROGRAM MAKAN BERGIZI GRATIS (MBG) DI SMPN 19 SURABAYA - Erizka Romadoni Amalia Putri; Eufrasia Kartika Hanindraputri (Jurnal Manajemen Pendidikan, 2026)
This research aimed to explore the stories of students participating in the MBG program at SMPN 19 Surabaya. The MBG program, launched and implemented, focused on increasing nutrient-rich intake for the target students, as well as maintaining healthy bodies so that students' minds remained focused on learning, resulting in strong academic achievement. This research employed a phenomenological approach, drawing on direct accounts from students. Data were collected through interviews, observations, and supporting documents. Informants were selected purposively, and the data was processed using the Miles and Huberman approach. The research found a shift toward positive outcomes, improving the students' well-being. They were encouraged to study harder, and healthy eating habits began to form. However, problems persisted, such as the menu not changing regularly and problems distributing food to students. The students consider the MBG program to be very meaningful and useful, so they see it not only as a matter of food intake but also as a way of creating a more positive atmosphere around them.